VALUES IN HUMAN LIFE AND SOCIETY - Gadoyeva Lobar Ergashevna (European International Journal of Pedagogics, 2023)
Eastern philosophy arose simultaneously with ancient philosophy. They are similar in genesis and issues, but differ from each other in the type of philosophizing. This is what became the determining factor in further development. In turn, this fact became the basis for believing that the philosophies of the East and the West are opposite to each other. This is not unreasonable, since there are differences in certain spheres of life: system, moral principles, culture, worldview.